Perencanaan Strategi Pengembangan Ruang Terbuka Hijau Kota Semarang (Studi Kasus : Hutan Wisata Tinjomoyo) - Sylvia Ayu Zuhaidha; Slamet Santoso; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Green open space is one of the important components to manage the city in order to realize the mandate of law Number 5 Year 2008. The implementation of the green open space in Semarang City hasn’t fully reached 30 %. Green open space has various type and benefits, one of them is theTinjomoyo Tourism Forest which the planning and management itself should involve Local Government Agencies of Semarang including Regional Development Planning Board and Departent of Cultural and Tourism.In making strategic planning of Green Open Space including Tinjomoyo Tourism Forest, it needs some things that support and great commitment of the parties involved, which is poured in the form of a initial agreement, understanding of the mandate in the Organization including the action that should be performed as well as regulatory support, alignment with the mission and purpose of which are owned by the identification of fulfilment, response to stakeholder, philosophy and the uniqueness of the Organization, assessment of external factors (political, economic, social and technological) and internal factors (resources, strategies, the effectiveness of performance) which subsequently obtained 7strategic issues identified and tested with litmus tests so that each of the formulation strategy obtained can be applied in the planning of the Green open spaces of Semarang, in particular Tinjomoyo Tourism Forest.To develop The Green Open Space can be done with the main strategy, that is cross-sector coordination, supported by other strategies that are improving the quality of human resources,harnessing the investor according to regulations, doing communication with all stakeholders including the public society, optimizing organizational performance through its vision and mission, taking advantage of the conducive political condition in Semarang city as well as the improvement of planning quality and budgeting of green open space, each of them is contained in the programs and activities that are relevant.